Sliding mode control for non-linear systems by Takagi–Sugeno fuzzy model and delta operator approaches - Wang, Jiahui; Gao, Yabin; Qiu, Jianbin; Ki Ahn, Choon (IET control theory & applications, 2017)
This study considers the problem of adaptive sliding mode control for discrete-time Takagi–Sugeno (T–S) fuzzy systems with actuator faults and external disturbances via the delta operator method. The delta operator approach is used to represent the discrete-time non-linear systems described by T–S fuzzy models. The actuator fault considered in this study is unknown and its fault-deviation is also unknown. A reduced-order system is utilised to design the sliding mode surface subject to linear matrix inequality constraint. By constructing the sliding mode surface, a novel adaptive sliding mode controller is designed to guarantee that the closed-loop system is uniformly ultimately bounded. Finally, two practical examples are presented to show the effectiveness and applicability of the developed fault-tolerant control scheme.